PERAN KEPUASAN KERJA DALAM MEMEDIASI PENGARUH STRES KERJA TERHADAP TURNOVER INTENTION DI KLINIK UTAMA BUNGA EMAS - Pradnyani, Dewa Ayu Putri Ari; Gede Supartha, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.10.TAHUN.2024DO - 10.24843/EEB.2024.v13.i10.p17, 2024)
Employee turnover is permanent, voluntary or involuntary resignation from an organization. The stage before actual turnover occurs is called turnover intention. This turnover intention can be caused by several factors, such as work stress and the level of job satisfaction. The aim of this research is to determine the role of job satisfaction in mediating the influence of work stress on turnover intention. This research was carried out at Klinik Utama Bunga Emas, with a sample size of 46 employees using the saturated sampling method. Data collection uses a questionnaire instrument. The data collected was then analyzed using path analysis. The results of the research show that work stress has a positive and significant effect on employee turnover intention at Klinik Utama Bunga Emas. Job satisfaction has a negative and significant effect on employee turnover intention at Klinik Utama Bunga Emas. work stress has a negative and significant effect on employee job satisfaction at Klinik Utama Bunga Emas. Job satisfaction is a complementary (partial mediation) mediating variable in the influence of work stress on employee turnover intention at Klinik Utama Bunga Emas. The implication of this research is that job satisfaction has an important role, where by increasing job satisfaction, high levels of work stress can be reduced and result in the level of turnover intention also decreasing. Apart from that, this research can be used as evaluation material in analyzing problems in companies, related to what factors influence turnover intention so that this research can be used as material for consideration in making managerial decisions and input for the company.